Safety Improvements through Lessons Learned from Operational Experience in Nuclear Research Facilities - Lambert, Francis; Volkov, Yuri.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
For operators of nuclear research facilities, it is of particular importance to investigate minor incidents: indeed, as safety demonstrations are generally based on the presence of several independent "lines of defence", only through attentive investigation of every occurrence, usually minor and of no consequence, can the level of trust placed in each of these defensive lines be confirmed, or the potential risks arising out of a possible weakness in the system be anticipated. The efficiency of the system is based on a rigorous procedure: stringent attention to all incidents, consideration of the potential consequences of the incidents in their most pessimistic scenarios, and promotion of a broad conception of transpositions of the events, in time and space, for experience feedback. This efficiency presumes motivation on the part of all those involved, hence the importance of dissociating from the concept of an "incident" any notion of "error" or "blame" both in internal analysis and in public communications. The nuclear industry has developed some very progressive tools for experience feedback, which could interest also management of other technological risks. This book presents the proceedings of a NATO Advanced Workshop dedicated to this important matter of concern.
HOW TO EXTRACT THE HIDDEN LESSONS FROM A SMALL INCIDENT ON A NUCLEAR RESEARCH FACILITY -- LEARNING FROM LOW LEVEL INCIDENTS -- THE EXPERIENCE OF EMERGENCY SHUTDOWN OF THE VVR-c REACTOR AFTER 40 YEARS OF OPERATION -- MINOR INCIDENTS DURING THE DECOMMISSIONING OF PROTOTYPE OPERATION AND RESEARCH FACILITIES OF THE KARLSRUHE RESEARCH CENTER -- ANALYSIS OF INFORMATION ON INCIDENTS AT RESEARCH NUCLEAR PLANTS IN RUSSIA -- PRACTICES IN GOVERNMENT REGULATION OF THE SAFETY OF RESEARCH NUCLEAR PLANTS IN RUSSIA -- SAFETY IMPROVEMENTS THROUGH LESSONS LEARNED FROM OPERATIONAL EXPERIENCE IN NUCLEAR RESEARCH FACILITIES -- THE RESPONSIBILITY OF HIGHER MANAGEMENT WITH RESPECT TO THE SAFETY POLICY OF RESEARCH CENTRES -- ORGANIZATION AND METHODS USED BY THE CEA SACLAY CENTRE TO IMPROVE OPERATING PROCEDURES AND PROMOTE BEST PRACTICES IN NUCLEAR RESEARCH FACILITIES -- ROLE OF THE HEALTH PHYSICS - SAFETY DEPARTMENT IN A NUCLEAR RESEARCH CENTRE SAFETY AS AN UNCEASING PROCESS: THE -- THE LESSONS OF 48 YEARS' OPERATION OF THE AM RESEARCH REACTOR -- SUMMARY OF THE GENERAL DISCUSSIONS.
Keywords: ENGINEERING; SYSTEM SAFETY; NUCLEAR ENGINEERING; ENVIRONMENTAL PROTECTION; ENVIRONMENTAL POLLUTION; ENGINEERING; QUALITY CONTROL, RELIABILITY, SAFETY AND RISK; FACILITY MANAGEMENT; NUCLEAR ENGINEERING; EFFECTS OF RADIATION/RADIATION PROTECTION; INDUSTRIAL POLLUTION PREVENTION